Concept of Housing and Settlement Development of Eco-Green-based Coastal Areas: A Case Study of Babelan and Tarumajaya, Bekasi, Indonesia - Zefri; Nurwahyi (Geography, Earth Science and Environment: Research Highlights Vol. 5, 2025)
In the coastal communities of the District Babelan and Tarumajaya Bekasi, daily life cannot be separated from dependency on infrastructure, public facilities and means of supporting the environment. The problem that is considered in this study is how the concept of structuring and developing housing and residential areas in coastal areas is based on eco-green and the purpose of arranging the concept of structuring and developing housing and residential areas in eco-based coastal areas so that the quality of the housing and settlement environment becomes better. The methodology used in this research was carried out on the basis of the actual conditions of housing and settlement areas in the study areas in Babelan District, and Tarumajaya as previously described in the discussion ahead, then combined with eco-green-based assessment parameters. The variables studied consisted of 8 (eight) components, namely: 1) Environmental Conditions, 2) Building Management, 3) Clean Water, 4) Wastewater, 5) Drainage, 6) Solid Waste, 7) Energy, and 8) Energy. Energy, and 8) Transportation. Based on the survey results and interviews, 1 housing unit is occupied by 2-3 families. This results in the number of residents in 1 house totaling between 8 - 11 people. The large number of families in 1 housing unit is based on a very close family relationship between parents and children, or brothers and sisters, even though they have their own families. Ownership of permanent housing is based on joint ownership with parents as the main owners. The co-living system shows that this is a common practice. Democratization in the family makes this habit a common thing. The physical character of the settlement as a coastal residential area is characterized by collective activities as fishermen. This activity is used as the identity of the settlement as a fishermen’s settlement which is implemented in the utilization of space both personally in one dwelling, as well as communal space along the coast in the settlement area. The routine of fishermen’s activities occurs continuously, thus making the coastal area a space that has activities throughout the day and night. In the context of settlements, the typology of functions as coastal settlements with fishermen’s activities shows a fairly thick difference. Based on the Eco-Green Concept in the arrangement and development of housing and settlements in coastal areas, including several things, namely: 1. green open space areas, including the concept of structuring riparian areas, namely the concept of improving the quality of settlements; 2. the concept of road network development; 3. the concept of handling waste; 4. the concept of handling clean water; 5. the concept of handling wastewater. It is recommended that planning for housing and settlement areas based on eco-green should also be adjusted to the potential and planning of coastal areas. It is also expected that the community and developers in the construction of housing and residential areas in the coastal area the concept of eco-green are absolutely condition so that damage can be avoided for the preservation of the housing and settlement environment itself.